Japan's imperial diplomacy : consuls, treaty ports, and war in China, 1895-1938 - Brooks, Barbara J., 1953-2013 (Studies of the East Asian Institute., 2000)
In November 1937, Ishii Itaro, head of the Japanese Foreign Ministry's Bureau of Asiatic Affairs, reflected bitterly on the decline of the ministry's influence in China and his own long and debilitating struggle to guide China policy. Ishii was the most notable member of a group of middle-level diplomats who, having served in China, strongly advocated that Japan adopt policies in harmony with China's rising nationalism and national interests. Japan's Imperial Diplomacy profiles this distinct strain of "China service diplomat", while providing a comprehensive look at the institutional history and internal dynamics of the Japanese Foreign Ministry and its handling of China affairs in the years leading up to and through the Second World War. Moving from a thorough examination of a wide range of primary sources, including the extensive archives of the Japanese Foreign Ministry, memoirs, diaries, and unpublished speeches, Japan's Imperial Diplomacy offers integrated interpretations of Japanese imperialism, diplomacy, and the bureaucratic restructuring of the 1930s that were fundamental to Japan's version of fascism and the move toward war